Pengaruh Dana Desa dan Alokasi Dana Desa terhadap Kinerja Pembangunan Desa - Imam Baidlowi (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Village development is a strategic priority in Indonesia because it supports equitable regional growth and improves community welfare. This study investigates the effects of the Village Fund and Village Fund Allocation on village development performance in Gedeg District, Mojokerto Regency. A quantitative design was used with secondary data collected from the Village Revenue and Expenditure Budget, budget realization reports, and other official government documents. The population included all villages in Gedeg District, so a census sampling technique was applied. The data were analyzed using multiple linear regression after meeting the classical assumption tests of normality, multicollinearity, heteroscedasticity, and autocorrelation. The results indicate that both the Village Fund and Village Fund Allocation have positive and significant effects on village development performance. The adjusted R² value of 0.573 shows that 57.3% of the variation in development performance is explained by these two fiscal variables, while the remaining 42.7% is influenced by other factors not examined in this study. These findings confirm that fiscal transfers contribute substantially to strengthening village development outcomes. Therefore, village governments should optimize the use of these funds through participatory planning, transparent implementation, and accountable financial management to ensure more effective and sustainable development. Future research should examine governance quality, human resources, and local economic conditions to capture other determinants of village development performance more comprehensively in Indonesia.